Sustainable art construction: Use of waste crush clay bricks as aesthetic interior and exterior art construction innovation / Muhammad Naim Mahyuddin ... [et al.] - Mahyuddin, Muhammad Naim; Ismail, Salleh; Husin, Azamuddin; Awang, Nor Nazida; Abd Rashid, Mohd Najib (2023)
In accordance with the globally spread trend of sustainability, the modern 4R concept of waste management promotes: reducing waste at the source, reusing elements and their parts, recycling to produce raw materials, and recovering embodied energy. Discarded bricks from building demolition sites studied in this study could be reused, but they could also be crushed and used as an application in aesthetic interior art façade. This paper investigates the use of waste crushed clay brick material as an aesthetic interior art façade panels with a stone face that can be used in a ventilated façade system. It describes the production process of a pilot element and goes on to suggest details of the proposed elements of the art facade. The paper also shows various design possibilities for application as well as observed aspects of sustainability and cost-effectiveness relevant to the application of the proposed interior art façade panel. The research contributes to the current course of sustainability in the construction industry by proposing an example of forming a new prefabricated building element using recycled building demolition waste material. Green building, also known as sustainable construction, is concerned with the fiscal, societal, and environmental effect of constructing a useful structure. In other words, it demands planners and builders to use construction practices that will not harm the ecosystem in the long run. Sustainable structures are intended to be energy effective, healthful for the people who reside or work in them, and to decrease pollution and trash.